Phase Ib study of anti-CSF-1R antibody emactuzumab in combination with CD40 agonist selicrelumab in advanced solid tumor patients. Issue 2 (23rd October 2020) - Machiels, Jean-Pascal; Gomez-Roca, Carlos; Michot, Jean-Marie; Zamarin, Dmitriy; Mitchell, Tara; Catala, Gaetan; Eberst, Lauriane; Jacob, Wolfgang; Jegg, Anna-Maria; Cannarile, Michael A; Watson, Carl; Babitzki, Galina; et al.
Abstract : Background: This phase Ib study evaluated the safety, clinical activity, pharmacokinetics, and pharmacodynamics (PD) of emactuzumab (anti-colony stimulating factor 1 receptor monoclonal antibody (mAb)) in combination with selicrelumab (agonistic cluster of differentiation 40 mAb) in patients with advanced solid tumors. Methods: Both emactuzumab and selicrelumab were administered intravenously every 3 weeks and doses were concomitantly escalated (emactuzumab: 500 to 1000 mg flat; selicrelumab: 2 to 16 mg flat). Dose escalation was conducted using the product of independent beta probabilities dose-escalation design. PD analyzes were performed on peripheral blood samples and tumor/skin biopsies at baseline and on treatment. Clinical activity was evaluated using investigator-based and Response Evaluation Criteria In Solid Tumors V.1.1-based tumor assessments. Results: Three dose-limiting toxicities (all infusion-related reactions (IRRs)) were observed at 8, 12 and 16 mg of selicrelumab together with 1000 mg of emactuzumab. The maximum tolerated dose was not reached at the predefined top doses of emactuzumab (1000 mg) and selicrelumab (16 mg). The most common adverse events were IRRs (75.7%), fatigue (54.1%), facial edema (37.8%), and increase in aspartate aminotransferase and creatinine phosphokinase (35.1% both). PD analyzes demonstrated an increase of Ki67 + -activated CD8 + T cells accompanied by a decrease of B cells and the reduction of CD14 Dim CD16 bright monocytes in peripheral blood. The best objective clinical response was stable disease in 40.5% of patients. Conclusion: Emactuzumab in combination with selicrelumab demonstrated a manageable safety profile and evidence of PD activity but did not translate into objective clinical responses. Trialregistration number: NCT02760797 .